The plight of foreign wife in marital disputes: extending the legal barriers - Mobarak Ali, Bashiran Begum; Mohd Zin, Najibah (IIUM Press, 2009)
Love knows no boundaries. Couples may come from different countries and settle down in the country of their choice. In most cases, the parties would prefer to return to the husband's family and stay on in his country. The wife, is an extremely a brave woman. She comes and settles in a country that is totally strange to her, right from the culture to the language. She has to adapt. There is no problem, if the husband understands and gives the entire moral, physical and financial support. However, what happens if the husband ignores, abused or divorced her! The question is what must she do or where can she go or whom can she rely upon for advise, especially when the language is a barrier to her? There have been cases too, where both husband and wife are foreigners, and the husband pronounced talak to the wife and left her. She is caught in a dilemma. Her marriage is not registered in Malaysia, neither is her divorce. What must she do? The purpose of this paper is to study, examine and analyze the sosio-legal issues and the challenges affecting foreign wife in a marital dispute in Malaysia. The perception is only the Embassy would understand her own people. So in this 21st century it is believed that the Embassy should play a more active role in providing solutions or advise to her subjects in a foreign country. So, the paper further aims to discuss on the role of Embassy as a stop centre in advising her subjects, especially wife in a marital disputes.